Complex Data Set Problem Solving With Hybrid Grid Partition And Rought Set Method For Fuzzy Rule Generation As A Solution - Mikstas Romantė Serksnas; Bučienė Naujienos Leganovic (International Enterprise Integration Association, 2020)
This research proposes a novel approach that combines hybrid grid partitioning and the rough set method for fuzzy rule generation to address the challenges posed by complex data set problem-solving. The approach aims to improve data representation, handle uncertainty, identify relevant features, extract dependency rules, and generate accurate fuzzy rules. The hybrid grid partitioning technique probabilistically assigns data points to cells based on local density, enhancing data representation and capturing variations in data density. The rough set method is applied within each cell to identify relevant features and extract dependency rules, considering the uncertainty and incompleteness present in the data. Fuzzy logic is incorporated to generate linguistically interpretable fuzzy rules that capture the complex relationships within the data set. The proposed approach offers an effective solution for complex data analysis, enabling enhanced decision-making, prediction accuracy, and understanding across various domains. However, the approach has limitations, including sensitivity to parameter selection, computational complexity, assumption of independence, interpretability of fuzzy rules, and generalizability to diverse domains. Further research and refinement are necessary to address these limitations and enhance the approach's performance and applicability. Overall, this research contributes to the field of complex data analysis by providing a comprehensive approach for problem-solving, with the potential to advance decision-making and understanding in complex data sets.